Impacto de la inmigración en la población económicamente activa ocupada del Perú periodo 2015-2019 - Murcia Ramírez, María del Carmen (2022)
Migratory flows cause distortion in the social, economic and labor fields, among others, even more so if it occurs in a large proportion. In this doctoral thesis, the aim is to determine the impact of immigration on the Economically Active Population of Peru, in the period 2015 - 2019. With this objective, the present investigation of Quantitative type, Correlational level and Non-Experimental design was carried out. The research concludes that immigration directly impacts the Economically Active Employed Population of Peru in the period 2015 - 2019, demonstrated by the result of the Correlation Coefficient that was r = 0.775553092. Likewise, it was demonstrated that foreigners residing in Peru are mainly Venezuelan nationals, since they added the number of 790,972 people, equivalent to 71.31% of the total; that is, almost ¾ parts of the total. On the other hand, the analysis of foreigners residing in Peru aged 14 and over according to occupation category, shows that "Trades" concentrates the largest number of workers by adding the amount of 187,257 people (19.55%), relegating in second place to "Professionals, Scientists and Intellectuals" with 133,235 people (13.91%). In the same sense, the predominant profession or occupation of foreigners residing in Peru in the five-year period under study corresponds to "Professional" with 52,301 workers (5.46%).